PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH (ICM) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII MTsTI BATANG KABUNG PADANG - Oktari Saputra, Hengki; Febriana, Rina; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACHÂ The background of The research was. This researchÂ  is motivated by the difficulty students answer the teacherâs question about the subject before and the lack of students understanding in mathematical concept with applying active learning strategy by Index Card Match to be better from the students mathematical concept with apply conventional learning at grade seventh of MTsTI Batang Kabung Padang of academic 2013/2014 years. This research is experimental research with the random design of subject. The population is the student seventh of MTsTI Batang Kabung Padang of academic 2013/2014 years. The sample has to with randomly the instrument are quiz and test. Based on the result of the research, quiz result increased each meeting. Based result of data analysis, it is know sample class is distribute normally and homogenously. So the hypothesis of the research will accept that mean is the understanding of student mathematical concept with apply active learning type Index Card Match with quiz is better from conventional learning at grade seventh of MTsTI Batang Kabung PadangÂ